Analisis Luas Wilayah Genangan dan Tinggi Banjir pada Proyek Rencana Kegiatan Superblok Kota Batam Menggunakan Aplikasi HEC-RAS 2D - Rahayu, Diana; Dewi, Endang Purnama; Purbakawaca, Rady; Rahayu, Sri; N/A, Elviana; Chumaedi, Irpan (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2025)
Floods are an annual disaster that disrupt public services and cause financial losses. Climate change and urbanization are the main factors contributing to increased rainfall which challenges the capacity of conventional drainage systems. The aim of writing this article is to analyze the depth, inundation area and flow direction in the superblock development plan using HEC-RAS 2D hydraulic modeling. The method used is to combine hydrological analysis, namely calculating the rainfall distribution using the Gumbel method, with hydraulic modeling. Hydrological analysis is conducted to calculate the frequency analysis of return periods and peak flood discharge. The return period rainfall using the Gumbel method for a 5-year return period (R5) is 212.921 mm. The flood discharge was calculated using the Rational method with catchment area 12.96 ha, resulting in Q = 1.08 m³/s. In calculating the Rational peak discharge, a rainfall intensity value is needed. The rain intensity required in the Rational method calculation uses the IDF curve to obtain a value of 100.6 mm/hour. The rain intensity value is then processed using an equation and the planned peak discharge is produced. Then peak flood discharge data is inputted and simulated using two-dimensional hydraulic modeling with HEC-RAS version 6.3.1 to obtain flood water surface profiles, inundation area and flow direction. The height of the flood inundation resulting from twodimensional hydraulic modeling using HEC-RAS 6.3.1 is 42 cm, the inundation area is approximately inundation area is around 8.5 ha, and the flow direction during flooding is towards the east of the project site.